Extreme hawser tension assessment for FPSO vessel during offloading operation in Bohai bay. (March 2021) - Gaidai, Oleg; Xu, Xiaosen; Sahoo, Prasanta; Ye, Renchuan; Cheng, Yong
Abstract: The Floating Production Storage and Offloading Unit (FPSO) is an offshore vessel that produces and stores crude oil prior to tanker transport. Robust prediction of extreme hawser tensions during Floating Production Storage and Offloading (FPSO) operation is an important safety concern. Excessive hawser tension may occur during offloading operations, posing an operational risk. In this paper, AQWA has been used to analyze vessel response due to hydrodynamic wave loads, acting on a specific FPSO vessel under actual sea conditions. Experimental validation of numerical results has been discussed as well. This paper advocates methodology for estimating extreme response statistics, based on simulations (or measurements). The modified ACER (averaged conditional exceedance rate) method is presented in brief detail. Proposed methodology provides an accurate extreme value prediction, utilizing all available data efficiently. In this study the estimated return level values, obtained by ACER method, are compared to the corresponding return level values obtained by Gumbel method. Based on the overall performance of the proposed method, it is concluded that the improved ACER method can provide more robust and accurate prediction of the extreme hawser tension. Data declustering issue has been addressed. Paper highlights ability of ACER method to account for a set of varying sea state probabilities, as required in engineering long term statistical analysis. Described approach may be well used at the vessel design stage, while defining optimal vessel parameters that would minimize potential FPSO hawser tension. Highlights: Extreme value statistics of FPSO- hawser tension forces has been studied. Statistical data clustering and narrow band effects discussed. Local environmental conditions in Bohai sea have been accounted for. The improved version of averaged conditional exceedance rate method has been applied. Results have been verified vs direct Monte Carlo simulation, as well as compared to another statistical method.